(3TQM GdSjQ GdcHjQs - (3CHh HcQ eMeO Hf CHi Sgd GdSQNSis; (3eMeO GdTjHGfj , eMeO Hf GdMSf GdTjHGfj, GdTjHGfjs
(3ChdgG (B:s
(3jHOC HHGH GdLgGO heG jSY efg heGdG jSY efg s
(3BNQgG (B:s
(3jfJgi HHGH GdYHO jYJb HESdGeg s
(3GdfSNI HgG MhGTs
(3GdfUa GdChds
(3Ydjg SeGYGJ SfI (B676 (3g`s
(3HgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdMfajs